Sharing Oil and Gas Revenue in Uganda - Muramira, Telly Eugene; Manyindo, Jacob (Uganda Wildlife Society, 2008)
Although Uganda has significant natural resource endowments, most communities living in proximity to these resources continue to suffer serious levels of poverty. This situation sets a bad precedent for the developing oil and gas sector. As a result, the Uganda Wildlife Society, with generous support from Irish AID through the World Resources Institute carried out this study to find practical ways local communities, local governments and the central government may fairly and equitably share revenue from oil and gas resources. The overall aim of the study was therefore to propose a revenue sharing formula and derivation fund for the oil and gas sector in Uganda. The specific objectives of the study were to: (i) define the concept of revenue sharing and derivation funds, its rationale and key features; (ii) review oil extraction models and oil revenue control; (iii) review existing institutional, policy and legal frameworks that have implications for the establishment of derivation funds and oil revenue sharing schemes; (iv) document relevant international experiences; (v) present the challenges, key measures and approaches to establishing a successful revenue sharing scheme and derivation fund for Uganda.